2018
DOI: 10.1002/anie.201811892
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Nuclear Polarization of 13C Nuclei in the Liquid State over a 10 Tesla Field Range

Abstract: Nuclear magnetic resonance (NMR) techniques play an essential role in natural science and medicine. In spite of the tremendous utility associated with the small energies detected, the most severe limitation is the low signal‐to‐noise ratio. Dynamic nuclear polarization (DNP), a technique based on transfer of polarization from electron to nuclear spins, has emerged as a tool to enhance sensitivity of NMR. However, the approach in liquids still faces several challenges. Herein we report the observation of room‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
74
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(93 citation statements)
references
References 34 publications
6
74
3
Order By: Relevance
“…[11][12][13][14][15] Furthermore, higher NMR enhancements could boost the applications of OE-DNP at low fields (o2 T), which include in-flow hyperpolarization for magnetic resonance imaging 16,17 or chromatography, 18,19 NMR relaxometry of low-g nuclei, 20 hydration dynamic studies, 21,22 and DNP-NMR spectroscopy. [23][24][25] In the experimental practice, nitroxide derivatives (NODs) have been established as optimal PAs for OE-DNP in the liquid state at room temperature and ambient pressure. 26,27 In water, they perform better than trityl radicals at various fields (from 0.34 T to 3.4 T), 28,29 and they are the benchmark for 1 H-DNP at low fields (enhancements e = À178 AE 13 for water doped with TEMPONE).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[11][12][13][14][15] Furthermore, higher NMR enhancements could boost the applications of OE-DNP at low fields (o2 T), which include in-flow hyperpolarization for magnetic resonance imaging 16,17 or chromatography, 18,19 NMR relaxometry of low-g nuclei, 20 hydration dynamic studies, 21,22 and DNP-NMR spectroscopy. [23][24][25] In the experimental practice, nitroxide derivatives (NODs) have been established as optimal PAs for OE-DNP in the liquid state at room temperature and ambient pressure. 26,27 In water, they perform better than trityl radicals at various fields (from 0.34 T to 3.4 T), 28,29 and they are the benchmark for 1 H-DNP at low fields (enhancements e = À178 AE 13 for water doped with TEMPONE).…”
mentioning
confidence: 99%
“…Despite the available data, it is difficult to compare the PA's performance independently of the experimental conditions, such as mw power and resonant cavity, magnetic field, radical concentration, and target nuclei. Although several mechanistic studies on 1 H 27,35,36 and 13 C 24,37,38 have been reported, the detailed role of the PA remains unclear. Very recently, we investigated the case of fullerene nitroxides in comparison to TEMPONE, 24,39 and found that small structural reorientations can impact the DNP efficiency at both low and high magnetic fields.…”
mentioning
confidence: 99%
See 3 more Smart Citations